ANALISIS PENGARUH BUDAYA KERJA DAN KOMPENSASI TERHADAP DISIPLIN KERJA - Wiella Ayu; Kustini Kustini (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
In this era of globalization, it is marked by competitive and risky economic developments. Every company competes each other for business positions by improving and developing the quality of their Human Resources (HR). Human Resources is an important aspect in the Company. The important thing to note is about employee discipline, people who are successful or achievers are usually disciplined. Success and accomplished people usually have good discipline. In a sense it has regularity. The main characteristic of discipline is well-organized. The purpose of this research is to find out: 1) The Effect of Work Culture on Work Discipline, 2) The Effect of Compensation on Work Discipline. The population of this research are the 32 employees of CV. Bumi Delta Makmur. The sample in this reserach is using a non-probability sampling technique by taking the sample by saturated sampling. Another term for saturated sampling is a census in which all members are sampled. The data used in this study are primary and direct data, and also interviews and company internal data. The analytical technique used in this research is Partial Least Square (PLS) analysis. Based on the research that has been done, it is obtained: 1) Work Culture has a positive and significant effect on Work Discipline, 2) Compensation has a positive and significant effect on Work Discipline.